Readings in the history of Christian theology ; v.1 - Placher, William Carl, 1948- (Phildelphia, PA Westminster, 1988)
Contents : v.1: From its beginnings to the eve of the Reformation. Includes bibliographical references and indexes.
Donated by The Australian College of Theology, 1996.
Keywords: Theology -- readings